Naofucong Ameliorates High Glucose Induced Hippocampal Neuron Injury Through Suppressing P2X7/NLRP1/Caspase-1 Pathway - Jing, Guangchan; Wang, Huanyuan; Nan, Fengwei; Liu, Yuqin; Zhang, Mengren (Frontiers in Pharmacology, 2021)
P2X7/NLRP1/caspase-1 mediated neuronal injury plays an important role in diabetic cognitive impairment and eventually inflammatory cascade reaction. Chinese herbal compound Naofucong (NFC) has been mainly used to treat cognitive disorders in Traditional Chinese Medicine (TCM). The present study aimed to investigate whether its neuroprotective effects might be related to the inhibition of P2X7R/NLRP1/caspase-1 mediated neuronal injury or not. In this study, high glucose-induced HT22 hippocampal neurons were used to determine Naofucong-containing serum neuronal protective effects. Lentiviruses knock out of TXNIP and P2X7R was used to determine that protective effects of Naofucong was related to inflammatory response and P2X7/NLRP1/caspase-1 mediated neuronal injury. NAC was also used to inhibit oxidative stress, so as to determine that oxidative stress is an important starting factor for neuronal injury of HT22 cells cultured with high glucose. Naofucong decreased apoptosis, IL-1β and IL-18 levels in high glucose-induced HT22 hippocampal neuron cells. Naofucong suppressed NLRP1/caspase-1 mediated neuronal injury, and P2X7 was involved in process. HT22 cells cultured in high glucose had an internal environment with elevated oxidative stress, which could promote neuronal injury. The current study demonstrated that Naofucong could significantly improve high glucose-induced HT22 hippocampal neuron injury, which might be related to suppress P2X7R/NLRP1/caspase-1 pathway, which provides novel evidence to support the future clinical use of Naofucong.